Pattern of Femoral Fractures - ObaidurRahman , Rana Muhammad Adnan , Rafeya Khan , Faiz ur Rahman , Muhammad Irfan Zia , Jahanzaib Amin , Imtiaz Ahmad ,Saleem Ahmed, (Journal of Rawalpindi Medical College, 2013)
Background: To assess the pattern of femoral fractures. Methods: In this descriptive study patients presenting with fracture of femur were enrolled. The relative frequencies of different fractures according to site and type of fracture, duration of hospital stay and gender and age based patterns of fracture incidence were analyzed. Results: There were 2232 patients with femoral fractures, comprising 39% of the complete patient load. Majority ( 64%) were males. Age incidence was bimodal. In younger patients (≤ 40 years of age) mid shaft of femur was the commonest region involved (79%) and road traffic accidents were the commonest mechanism of injury (86%). In older patients (> 40 years) pertrochanteric fracture was the commonest fracture (62%) and low energy falls were the commonest cause (62%). Average stay in hospital of patients with proximal femur fractures was 11 + 5 days and that of shaft was 14 + 7 days. Conclusion: The fractures in the young patients were predominantly due to motor vehicle accidents, whereas the fractures in elderly often result from low energy falls, indicating presence of prior predisposition